The Effectiveness of Aggression Replacement Training Program on Antisocial Behaviors, Anger Rumination of Adolescence Girls in Ahwaz - Faride Ensafdaran; Soodabeh Bassak Njad; Nasrin Arshadi (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Aggression is one of the main focuses of research activities of psychologists and psychiatrists, and a significant proportion of those referring to psychiatric and psychiatric centers have aggression problems. The purpose of this study was to determine the effectiveness of Aggression Replacement Training  (ART) program on antisocial behaviors  (physical aggression, social aggression and rule breaking) and anger rumination in Ahwaz adolescent girls. Methods: The research method was a randomized clinical trial design. A sample of 45 students who entered the research were selected through a step-by-step sampling method among the four educational districts of Ahvaz and randomly assigned to three groups of experimental, placebo and control. Tools included Burt & Donnellan's antisocial behavior questionnaire and S Sukhodolsky's rumination questionnaire. Also, for analyzing the data, SPSS 18 was used and the level of significance was 0.05. Results: There was a significant difference between the mean of experimental, placebo and control groups in the dimensions of antisocial behaviors and anger rumination  (F=23.54 and P=0.01). Conclusion: Aggression Replacement Training program reduces antisocial behaviors and anger rumination in adolescent girls, so it can be used in schools and centers to prevent and reduce aggressive and anti-social behaviors.